1999
DOI: 10.3354/meps177165
|View full text |Cite
|
Sign up to set email alerts
|

Retention of ciliates and flagellates by the oyster Crassostrea gigas in French Atlantic coastal ponds:protists as a trophic link between bacterioplankton and benthic suspension-feeders

Abstract: Retention of ciliates and flagellates by the oyster. In order to evaluate the importance of the 'protozoan trophic link' for energy transfer from the 'microbial food web' to large benthic suspension feeders, we offered a coastal pond comn~unity of ciliates and flagellates as potential prey to the oyster Crassostrea gigas. Clearance rate, filtered particles and relative retention efficiency were evaluated. In the grazing experiment, 94 % of ciliates and 86% of flagellates (size between 4 and 72 pm), were retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 30 publications
4
73
0
Order By: Relevance
“…Enumeration of ciliates and flagellates-Ciliates and flagellates were fixed, stained, and enumerated according to Dupuy et al (1999). This method is a modified version of the method previously described by Haas (1982), Caron (1983), and Sherr et al (1994).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Enumeration of ciliates and flagellates-Ciliates and flagellates were fixed, stained, and enumerated according to Dupuy et al (1999). This method is a modified version of the method previously described by Haas (1982), Caron (1983), and Sherr et al (1994).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Previous studies have indicated that particles <2 µm in diameter are generally inefficiently consumed by bivalves (Ward et al 1998;Dupuy et al 1999) and studies currently being undertaken indicate that this is also true for P. canaliculus (authors' unpubl. data).…”
Section: Resultsmentioning
confidence: 99%
“…The phytoplankton community was divided into microphytoplankton (20-200 µm), nanophytoplankton (2-20 µm), and picophytoplankton (0.2-2 µm) size classes according to the scale of Sieburth et al (1978). The nanophytoplankton (2-20 µm) were further divided into two size ranges, 2-5 and 5-20 µm, to cover feeding retention size ranges as described by Ward et al (1998) and Dupuy et al (1999).…”
Section: Methodsmentioning
confidence: 99%
“…3) is in good agreement with the literature. Using an allometric exponent of 0.73 (Riisgård 1988), the clearance rate for an oyster (3.9 g) can from the literature be calculated to 10.2 L h -1 (Bougrier et al 1995), 8.2 L h -1 (Ren et al 2000), 10.8-19.4 L h -1 (Dupuy et al 1999), and for Crassostrea virginica 18.4 L h -1 (Riisgård 1988).…”
Section: Discussionmentioning
confidence: 99%